2014
DOI: 10.1016/j.febslet.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Induction of microRNA‐138 by pro‐inflammatory cytokines causes endothelial cell dysfunction

Abstract: Exposure to pro-inflammatory cytokines, such as angiotensin II, endothelin-1 or TNF leads to endothelial dysfunction, characterized by the reduced production of nitric oxide via endothelial nitric oxide synthase (eNOS). We recently identified the Ca2+ binding protein S100A1 as an essential factor required for eNOS activity. Here we report that pro-inflammatory cytokines down-regulate expression of S100A1 in primary human microvascular endothelial cells (HMVECs) via induction of microRNA-138 (miR-138), in a man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 48 publications
0
29
0
2
Order By: Relevance
“…Hypoxia/ischemia stimulates EPCs to migrate from the bone marrow into the peripheral blood, adhere to the endothelium at sites of hypoxia/ischemia and participate in new vessel formation by differentiating into ECs (21). miR-138 may be involved in the regulation of hypoxia-induced EC dysfunction (22); however, to the best of our knowledge, the exact role of miR-138 in mediating EPC proliferation under hypoxia has not been studied. The present study demonstrated that miR-138 significantly suppressed the hypoxia-induced proliferation of EPCs, possibly by inducing cell cycle arrest at the G1 stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia/ischemia stimulates EPCs to migrate from the bone marrow into the peripheral blood, adhere to the endothelium at sites of hypoxia/ischemia and participate in new vessel formation by differentiating into ECs (21). miR-138 may be involved in the regulation of hypoxia-induced EC dysfunction (22); however, to the best of our knowledge, the exact role of miR-138 in mediating EPC proliferation under hypoxia has not been studied. The present study demonstrated that miR-138 significantly suppressed the hypoxia-induced proliferation of EPCs, possibly by inducing cell cycle arrest at the G1 stage.…”
Section: Discussionmentioning
confidence: 99%
“…Nishimura et al (23) reported that hypoxia induced the proliferation of tissue-resident EPCs in the lung. Furthermore, Sen et al (22) indicated that exposure to pro-inflammatory cytokines, including angiotensin II, endothelin-1 and tumor necrosis factor, may result in EC dysfunction and the downregulation of S100A1 expression by inducing miR-138 in a manner dependent on the stabilization of HIF-1α. This suggests that miR-138 is involved in EC dysfunction (22).…”
Section: Discussionmentioning
confidence: 99%
“…They induce EC p38 and JNK activation, increase immune cell adhesion molecule expression, promote VSMC migration, and cause EC barrier dysfunction, all of which further accelerate local inflammation (38,39). A number of studies have determined that heparin exhibits anti-inflammatory properties and modulates angiogenesis (1).…”
Section: Discussionmentioning
confidence: 99%
“…TNF␣ has been shown to inhibit endothelial nitrous oxide synthase activity and, as a result, decrease NO production, which would lead to lower levels of active cGMP-dependent protein kinase. This causes ECs to become vasoconstrictive and, eventually, dysfunctional (38,57). Recent studies have shown that the effects of heparin in VSMCs involve cGMP-dependent protein kinase (22).…”
Section: Discussionmentioning
confidence: 99%
“…miR-376b was reported to inhibit angiogenesis by targeting the VEGFA/Notch1 signaling pathway . A functional link between upregulation of miR-138 and endothelial dysfunction has also been proposed (Sen et al 2014).…”
Section: Discussionmentioning
confidence: 99%